Angelica sinensis polysaccharide prevents mitochondrial apoptosis by regulating the Treg/Th17 ratio in aplastic anemia - Zetao Chen; Li Cheng; Jing Zhang; Xing Cui (BMC, 2020)
Abstract Background Angelica sinensis polysaccharide (ASP) is an effective medicine for aplastic anemia (AA). The present study aims to investigate whether mitochondrial apoptosis in aplastic anemia could be corrected by ASP by adjusting an abnormal level of regulatory T cell (Treg)/ IL-17 secreting CD4 T cell (Th17) ratio. Methods BALB/c mice were treated with 5.0 Gy Co60 γ -radiation. Then 2 × 106 lymph node cells from DBA/2 donor mice were transplanted within 4 h after radiation. The mice in the various groups were fed saline or ASP for 2 weeks. For the in vitro experiment, bone marrow nucleated cells (BMNCs) and Treg cells were sorted from the mice on the 2nd day of modeling, and then cultured with or without ASP. Results The mice treated with the medium dose of ASP for 14 days showed increased white blood cell (WBC), red blood cell (RBC), platelet (PLT), BMNC counts and Lin-Sca-1 + c-Kit+ (LSK) populations viability compared with the mice in the AA group mice. The data showed that ASP decreased damage to the mitochondrial outer membrane, improved the stabilization of the mitochondrial membrane, and corrected the abnormal levels of ROS and mitochondrial-associated apoptosis proteins, including the Bcl-2/Bax ratio and caspase-3 and caspase-9 expression, in BMNCs which were sorted from the bone marrow cells of AA mice. The changes to the p-P38/P38 and Treg/Th17 ratios induced by AA were also reversed by the medium dose of ASP. The same ASP effect including the Bcl-2/Bax and p-P38/P38 ratio, caspase-3 and caspase-9 expression of BMNCs were observed in vivo. The viability of Treg cells were increased by treatment of ASP in vivo. Conclusions ASP might prevent mitochondrial apoptosis to restore the function of hematopoietic stem cells by suppressing abnormal T-cell immunity in AA.